Epigenetic reprogramming by TET enzymes impacts co-transcriptional R-loops - Sabino, João C. (2022)
PTDC/BIA-MOL/30438/2017 PTDC/MED-OUT/4301/2020 RiboMed 857119 PD/BD/128292/2017 LCF/PR/HP21/52310016 PTDC/BIA-MOL/6624/2020 PTDC/MED-ONC/7864/2020